Nostalgia for the British Era: Poststructuralist Critique of the Modernist Discourse of ‘Civilization’ in the Turkish Cypriot Media - Beyazoğlu, İbrahim (Eastern Mediterranean University EMU, 2016)
This study opens up a vista onto the notion popular among a growing number of Turkish Cypriots that the British colonial period brought modernist enlightenment to Turkish Cypriots. Turkish Cypriots were subject to heavy Turkish immigration from 1974 onwards as well as Turkish authorities mandating Turkish nationalism over the native politics and value system. In response, Turkish Cypriots have harkened back nostalgically to the British inheritance in their search for the universal standards of a “metahistoric” civilization. In doing so, Turkish Cypriots constructed a nostalgic nationalist movement called Cypriotism, an “identity of difference” that stands in binary opposition to the so-called “backward” immigrants to the island from Turkey, and to Turkish nationalism. Using postcolonial theory, this study critically analyses the media constructions of nostalgic nationalism in local Turkish-Cypriot media in the light of historic landmarks and milestones. Keywords: Nostalgia, Colonialism, Post-colonialism, Nostalgia, Nostalgic Media Constructions, Modernist Thought, White Mythology, the Turkish Cypriots, Textuality.

ÖZ: Bu çalışma, giderek artan sayıda Kıbrıslı Türk arasında popülerlik kazanan İngiliz sömürge döneminin Kıbrıslı Türklere aydınlanma getirdiğini varsayan modernist metinsel dokuma üzerine kavramsal ve analitik bir pencere açar. 1974 sonrası deneyimlenen Türkiyeli göçmenlerle yaşanan iletişim sıkıntıları ve adanın yerlileri ve değer sistemleri ile etkileşime geçen “buyurgan” Türk milliyetçiliği söylemleri, bu durumdan rahatsız birçok Kıbrıslı Türk’ün “tarihötesi” olduğu düşünülen İngiliz sömürge uygarlığı ve mirasının evrensel standartlarına nostaljik bir “geri dönüş” yapmasına yol açtı. Bu minvalde, geniş bir politik ve kültürel yelpazeye yayılan Kıbrıslı Türk Kıbrıslılık adlı nostaljik milliyetçi bir yapıyı, “bir ayırıcı hüviyeti” inşa edip söz konusu kimliği Türkiye’den gelip adaya yerleşen göçmenlere ve Türk milliyetçi söylemine karşı ikili zıtlık zemininde konuşlandırdı. Postkolonyal teoriyi kullanan bu tez sömürge-sonrası Kıbrıs Türk medyasının nostaljik milliyetçilik kurgularını, tarihi dönüm noktalarını ve kilometre taşlarını da gözden kaçırmadan, eleştirel bir incelemeye tabi tutar. Anahtar Kelimeler: Nostalji, Sömürge, Sömürge-Sonrası, Nostaljik Medya Kurguları, Modernist Düşünce, Beyaz Mitoloji, Kıbrıslı Türkler, Metinsellik.
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Assoc. Prof. Dr. Tuğrul İlter.
Keywords: Communication and Media Studies; British Rule-Modernist Enlightenment-Turkish Cypriots-Cyprus; British Rule-Post-Colonialism-Turkish Cypriots-Civilization; Nostalgia; Colonialism; Post-colonialism; Nostalgic Media Constructions; Modernist Thought; White Mythology; the Turkish Cypriots; Textuality